A rapid in‐house validated GC‐FID method for simultaneous determination of lipophilic bioactives in olive oil: Squalene, α‐tocopherol, and β‐sitosterol. Issue 1 (28th April 2016) - Seçmeler, Özge; Güçlü Üstündağ, Özlem
Abstract : The analytical methodologies utilizing HPLC or GC techniques for the determination of predominant lipophilic bioactives in olive oil (β‐sitosterol, squalene, and α‐tocopherol) may include a number of sample pre‐treatment steps (such as clean up (using TLC and SPE), saponification, and derivatization) making them rather lengthy and impractical. The objective of this study was to develop a rapid and in‐house validated GC‐FID method for the simultaneous determination of these bioactives using response surface methodology for optimization of critical parameters (time and temperature of saponification and derivatization). In‐house method validation based on method performance parameters (linearity, limit of detection (LOD), limit of quantification (LOQ), repeatability, and recovery) was carried out using optimized method parameters (10 min derivatization time for 30°C derivatization temperature, 56°C saponification temperature, and 10 min saponification time). The linear range of β‐sitosterol, squalene, and α‐tocopherol was determined to be between LOQ value (8.4; 16.0; 12.5 mg/100 g, respectively) and upper end (500; 700 mg/100 g for β‐sitosterol; squalene, respectively) with acceptable accuracy, recovery (92–97%; 93–95%; 93–110%) and repeatability. Practical applications: The in‐house GC‐FID method developed in this study offers a rapid, accurate and validated method alternative to current official methods and simultaneous methods recently published in the literature. Time of analysis was reduced to ∼5 h for every six samples compared to ∼20 h specified in official methods. The developed method was fully validated covering all parameters; linearity, LOQ, LOD, recovery, and repeatability. This method can be incorporated into quality control programs for olive oil and its application areas can be expanded to include other plant oils after further validation studies. A new rapid multicomponent in‐house validated method was developed to determine predominant lipophilics of olive oil. Abstract : A new rapid multicomponent in‐house validated method was developed to determine predominant lipophilics of olive oil.